The value of the key pass in modern football: statistical evidence in the Italian a series - Cusano, P.; Ascione, A. (Sport Science - International Scientific Journal of Kinesiology, 2019)
The importance of the number of key passes detected in a football match is becoming increasingly important in the specificity of the match analysis in football. Determining this index allows obtaining extremely significant data about the offensive dangerousness and the technical characteristics of some of the athletes of a team, during the game observation phase. Ball possession understood as a statistical index of the predominance of one team over another is related to the index of key passes expressed to understand how their correlation is effective and relevant to the positive outcomes reached by the team. This research can highlight the usefulness of the connection between the two reference values in the analysis of the tactical football performance. The search for data is carried out in a portion of the Italian football championship, and allows us observing significant elements and evaluating the link with the outcomes expressed by the team. This examination represents an innovative point of observation in the specific statistical analysis of this discipline, and could be of considerable advantage in subsequent scientific research.